PENGARUH VARIABEL JUMLAH PERUSAHAAN, PEMBELIAN BARANG MODAL TETAP DAN JUMLAH TENAGA KERJA TERHADAP OUTPUT INDUSTRI MAKANAN, MINUMAN DAN TEMBAKAU DI INDONESIA - Suprapto Suprapto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2008)
The study analysed food, beverage, and tobacco firms (classified as ISIC 31) in Indonesia during 1992-2006. It aimed to find out the effect of number of firm, purchase of fixed capital and number of employee on the ouput of food, berverage, and tobacco industries simultaneously as well as partially on the industries ouput; find out the efficiency and returns to scale of those industries.The results showed that all variable simultaneously influenced the put of those industries. Partially the effect of the number of firm and the purchase of fixed capital were significant, but number of employee was insignificant. The higher number of firm and fixed capital, the higher the industry out put. Further more the study found that those industries have not been effivent and have been in increassing return to scale as shown by their respective regression soefficient in increassing return to scale as shown by their resprective regression coefficient which were more than one.